EFFECTIVENESS OF CLOSURE OF HOLE USING A TOOTH FRAGMENT (Medical science of Uzbekistan, 2023)
This research work is aimed at studying the effectiveness of the method of using a tooth fragment to preserve the alveolar process during tooth extraction. Based on a review of the literature and analysis of modern clinical studies, key aspects of the effectiveness of the method were identified. Analysis of the structural stability of the alveolar process, functional results, as well as assessment of long-term consequences after using this method became the main directions of research.